2020
DOI: 10.7554/elife.61968
|View full text |Cite
|
Sign up to set email alerts
|

Metage2Metabo, microbiota-scale metabolic complementarity for the identification of key species

Abstract: To capture the functional diversity of microbiota, one must identify metabolic functions and species of interest within hundreds or thousands of microorganisms. We present Metage2Metabo (M2M) a resource that meets the need for de novo functional screening of genome-scale metabolic networks (GSMNs) at the scale of a metagenome, and the identification of critical species with respect to metabolic cooperation. M2M comprises a flexible pipeline for the characterisation of individual metabolisms and collective meta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 107 publications
0
60
0
1
Order By: Relevance
“…Therefore, Prokka v1.14.6, 98 was used to annotate the 119 unannotated genomes as a preliminary step. Pathway predictions were then performed for all 336 genomes with mpwt v0.5.3 multiprocessing tool, 99 for the PathoLogic pipeline of Pathway Tools 23.0. 100 Pathways for ethanol and short chain fatty acid (acetate, butyrate, propionate) production, bile acid metabolism, and choline degradation to trimethylamine were identified from MetaCyc pathway classifications (see ref.…”
Section: Pathway Inference For Taxa Associated With Flimentioning
confidence: 99%
“…Therefore, Prokka v1.14.6, 98 was used to annotate the 119 unannotated genomes as a preliminary step. Pathway predictions were then performed for all 336 genomes with mpwt v0.5.3 multiprocessing tool, 99 for the PathoLogic pipeline of Pathway Tools 23.0. 100 Pathways for ethanol and short chain fatty acid (acetate, butyrate, propionate) production, bile acid metabolism, and choline degradation to trimethylamine were identified from MetaCyc pathway classifications (see ref.…”
Section: Pathway Inference For Taxa Associated With Flimentioning
confidence: 99%
“…Another application of metabolic complementarity using different annotation pipeline could also be in the context of metagenome analysis, on Metagenome Assembled Genomes (MAGs) of uncultured bacteria. Belcour et al (2020) have shown that reconstructed metabolic networks from MAGs are similar to the reference genomes. Also, the stability of the producible metabolites and selected minimal symbionts was demonstrated for degraded genomes with 2% of genes randomly removed.…”
Section: Discussionmentioning
confidence: 89%
“…To be able to use this metabolic network of the host for complementarity analyses, the same version of Pathway Tools was also used to reconstruct the bacterial draft metabolic networks. For each annotated bacterial genome (i.e., 5 pipelines × 81 strains), a draft metabolic network was automatically reconstructed using Mpwt, the PathoLogic multiprocessing wrapper Python package ( Belcour et al, 2020 ) taking into account the protein description, GO terms, and complete EC numbers. The output files created by Pathway Tools were then converted to the SBML format with the Padmet software.…”
Section: Methodsmentioning
confidence: 99%
“…Metagenomic shotgun sequencing is more expensive but has advantages compared to 16S rRNA gene sequencing 24 : it not only reveals the composition of the gut microbiome but also the functions encoded by the genes in the microbiome 25,26 . Bioinformatic tools that analyze shotgun sequencing data for different purposes-taxonomic classification of microbial composition 27 , gene abundance prediction of specialty genes such as antibiotic resistance 28,29 and virulence factors 29 , genome identification of strain-level or species-level metagenome-assembled genomes (MAGs) 30,31 and metabolic model reconstruction that translate the DNA sequences to biochemical reactions [32][33][34] -are now readily available. Some of these tools even work directly with the accession numbers of the sequencing data deposited in public repositories, which greatly facilitates analysis.…”
Section: Background and Summarymentioning
confidence: 99%